The Legal Effects of Civil Liability Arising from the Practice of Licensed Radiological Activity - Majid Thamer, Researcher. Zainab; Majid Jasim, Assist .Prof. Batool (Basra studies journal, 2025)
Civil liability is one of the most important legal topics, as it addresses cases in which individuals suffer harm due to the fault of a responsible party an outcome dictated by principles of justice: whoever causes harm must remedy it. In the context of practicing licensed radiological activity, whose applications have expanded across medical, industrial, agricultural, and communications fields, the resulting harm can extend to the environment in all its components, including human health and safety. This necessitates legislative intervention to ensure legal protection by establishing civil liability for damages arising from radiological activities. This study aims to highlight the legal foundation of such liability and the challenges of relying on fault-based civil liability in these cases. It also explores the unique characteristics of harm caused by radiological activity, and addresses the extent to which public administration may bear responsibility for compensation whether wholly or partially on behalf of the licensed individual operating the radiological activity.